1999
DOI: 10.1073/pnas.96.13.7196
|View full text |Cite
|
Sign up to set email alerts
|

Poisoning of human DNA topoisomerase I by ecteinascidin 743, an anticancer drug that selectively alkylates DNA in the minor groove

Abstract: Ecteinascidin 743 (Et743, National Service Center 648766) is a potent antitumor agent from the Caribbean tunicate Ecteinascidia turbinata. Although Et743 is presently in clinical trials for human cancers, the mechanisms of antitumor activity of Et743 have not been elucidated. Et743 can alkylate selectively guanine N2 from the DNA minor groove, and this alkylation is reversed by DNA denaturation. Thus, Et743 differs from other DNA alkylating agents presently in the clinic (by both its biochemical activities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 28 publications
0
50
0
Order By: Relevance
“…DNA containing partially singlestranded regions and extra-helical segments (bulges) were shown to be cleaved by the enzyme (26,43,44). Top1 also cleaves DNA sites with local structure distortion including oxidative base modifications (36), base mismatches and abasic sites (45), UV photoproducts (46), base methylation (47), intercalation (48), and minor groove alkylation (49,50). Top1 has also been found to cleave three-stranded flap regions and promote their DNA recombination (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…DNA containing partially singlestranded regions and extra-helical segments (bulges) were shown to be cleaved by the enzyme (26,43,44). Top1 also cleaves DNA sites with local structure distortion including oxidative base modifications (36), base mismatches and abasic sites (45), UV photoproducts (46), base methylation (47), intercalation (48), and minor groove alkylation (49,50). Top1 has also been found to cleave three-stranded flap regions and promote their DNA recombination (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Other compounds that a ect minor groove DNA binding such as distamycins are known to be reactive in AT-rich regions suggesting an overall gene regulation impairment by such agents (Broggini et al, 1989). Through DNA minor groove alkylation, ET-743 also induces topoisomerase I mediated DNA strand breaks (Takebayashi et al, 1999). Additionally, ET-743 also appears to indirectly disorganize microtubule formation (Garcia-Rocha et al, 1996).…”
Section: A Minor-grove Dna Inhibitor Et-743mentioning
confidence: 99%
“…97 ͉ no. 12 ͉ 6775-6779 bule disruption (13), and target topoisomerase I (14,15), its mechanism of action in vivo is unknown. A recent study showed that ET-743 interfered with the interaction of minor-groove-binding proteins, particularly NF-Y, with their cognate DNA elements in vitro (16).…”
mentioning
confidence: 99%